Motivation and attitudes towards learning english: A study of petroleum engineering undergraduates at Hadhramout University of sciences and technology - Atef Al-Tamimi; Munir Shuib (Penerbitan UKM, 2009)
This paper outlines the results of a survey which was carried out, to identify Petroleum Engineering students’ motivation and attitudes towards learning the English language. The study investigated students’ motivation in terms of three motivational constructs: instrumental motivation, integrative motivation and personal motivation based on Gardner’s (1985) and Cooper and Fishman’s (1977) works. Learners’ attitudes, on the other hand, regarding 1) the use of English in the Yemeni social context, 2) the use of English in the Yemeni educational context, 3) the English language and 4) the culture of the English speaking world were identified. The study sample consisted of 81 petroleum engineering students at Hadhramout University of Sciences and Technology (HUST). A questionnaire and interviews were used for data collection. For the students’ motivation, the findings showed the subjects’ greater support of instrumental reasons for learning the English language including utilitarian and academic reasons. Personal reasons were also regarded as important motives by the students. However, regarding the integrative reasons, the results provided evidence that learning English as a part of the culture of its people had the least impact in students’ English language motivation. On the other hand, data for the students’ attitudes revealed that most of students had positive attitudes towards the social value and educational status of English. In addition, the findings showed the students’ positive orientation toward the English language. Interestingly enough, the results indicated that a high number of the students showed their interest in the culture of the English speaking world as represented by English-language films. Finally, some pedagogical implications that would help tap the students’ motivation and attitudes were presented